Saudi adolescents’ perceptions of dietary contributions to obesity: A qualitative study - Nasser S. Alqahtani (PLoS ONE, 2025)
Background Adolescents’ perceptions of the dietary effects of obesity play an imporant part in shaping their eating behaviors, lifestyle choices, and overall health outcomes. Their beliefs and attitudes surrounding diet and obesity can significantly influence food intake, nutritional habits, and levels of physical activity. This study aimed to examine adolescents’ perceptions of how diet contributes to obesity. Materials and methods This qualitative, prospective observational study included 62 adolescents of 12‒18 years old who were categorized as overweight or obese. Selection of participants was through purposive convenience sampling. Data were gathered through interviews and analyzed using Microsoft Office Excel tools. Results Five primary themes emerged from the analysis: (1) determinants of obesity, (2) strategies for obesity prevention, (3) educational and health system factors, (4) stigma associated with being overweight, and (5) perceived health risks due to obesity. The most cited factor contributing to obesity was the widespread availability of unhealthy food. Participants also noted weak school policies, experiences of being stigmatized (e.g., teasing and diminished self-esteem), and concerns about the health risks associated with obesity. Prevention strategies emphasized the importance of motivation, awareness, and institutional support. Conclusion Adolescents identified the accessibility of fast food and a lack of knowledge as major contributors to obesity. Weak school and health policies were also noted as contributing factors. Being stigmatized, particularly in the form of mocking, emerged as the most prominent social challenge. Participants believed obesity increases disease risks and highlighted individual motivation as important in prevention efforts. The findings highlight the need to promote healthy habits and strengthen awareness among adolescents.